2020
DOI: 10.5771/0949-6181-2020-4-608
|View full text |Cite
|
Sign up to set email alerts
|

Do the burst of financial crisis and European Union membership impact Earnings Management. Evidence from emerging Eastern European countries

Abstract: The paper studies earnings management in developing European countries. We investigated if membership in the European Union and the recent global financial crisis affected the decisions of managers in Eastern European countries to engage in earnings management. By analyzing a sample of 4,627 firms from four developing Eastern European countries (the Czech Republic, Poland, Hungary, and Slovakia) over the period of 2002-2009, our findings suggest there was a decrease in earnings management over the period leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Orlowski provided evidence that deeper integration of capital markets in the European Union actively contributes to real GDP growth [ 22 ]. Callao et al found that after joining the EU, it is conducive to earnings management and benefits the enterprise by analyzing a sample of 4,627 firms from four developing Eastern European countries [ 23 ]. However, Vermeulen researched the negative impact of EU eastern enlargement on the performance of SMEs in the new border areas [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Orlowski provided evidence that deeper integration of capital markets in the European Union actively contributes to real GDP growth [ 22 ]. Callao et al found that after joining the EU, it is conducive to earnings management and benefits the enterprise by analyzing a sample of 4,627 firms from four developing Eastern European countries [ 23 ]. However, Vermeulen researched the negative impact of EU eastern enlargement on the performance of SMEs in the new border areas [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nordhaus (2018) believes that the economic growth rate of 3% represents a level for maintenance, which depends on labr freedom, monetary freedom and trade freedom, as elements of economic freedom. According to Nordhaus & Boyer (2000), analyzing trends showed that economic freedoms influence the exit from the crisis, and then the growth and development of the country (Nordhaus & Boyer, 2000;Radovanović, Grandov & Filijović, 2019;Callao, Jarne, Wroblewski, 2020). Based on their research, Gregory, Romer and Weil (1992) believe that the growth of financial performance in retail development depends on the integrity of the government in the creation of economic policies, which represents the parameters of economic freedom and foreign direct investment.…”
Section: Review Of the Literature And Previous Researchmentioning
confidence: 99%
“…Among them, K is the number of types of covariates, O k represents the observation frequency of the k-th covariant type, E k represents the prediction frequency of the k-th covariant type, and the degree of freedom is the difference between the number of covariate types and the number of parameters [5].…”
Section: Statistics and Aimentioning
confidence: 99%